Dieta hipoproteica-hiperglicídica aumenta o consumo alimentar de ratos em fase de crescimento pela redução de OB-R e POMC no hipotálamo - Froelich, Mendalli (2013)
Objective: Our objective in this study was to evaluate the resistance to leptin in rats in growing phase after the administration of low protein-high carbohydrate (LPHC) diet during 15 days and in the adult rats that after 15 days continued to be submitted to LPHC diet and rats that had the diet exchanged by control diet for another 30 days. Methods and Results: Male Wistar rats with 30 days of age and weighing 100g were randomly divided into five groups: i) C15 - included rats fed a C diet (17% of protein, 63% carbohydrate and 7% lipid) for 15 days; ii) LPHC15 – included rats fed an LPHC diet (6% of protein, 74% carbohydrate and 7% lipid) for 15 days; iii) C45 - included rats fed a C diet for 45 days; iv) LPHC45 -included rats fed an LPHC diet for 45 days; v) R group, included rats fed an LPHC diet during the first 15 days and then the LPHC diet was replaced by a control diet for another 30 days. After the sacrifice were collected blood samples for hormone determination by Elisa and hypothalamus to evaluate the content of the leptin receptor (ObRb) and of the proteins of the leptin signaling pathways (JAK2, p-JAK2, STAT3, p-STAT3, SOCS3), of the neuropeptides (NPY, POMC) and (AMPK, p-AMPK) by Western blot. Data are expressed as mean ± standard error (p<0.05) using one-way ANOVA or Student’s t test. LPHC15 group showed increase in serum leptin levels with reduction in content of the leptin receptor (ObRb) and POMC content when compared to C15 group. LPHC45 and R groups showed the content of all proteins evaluated similar to C45 group, however the group LPHC45 showed elevated levels of adiponectin compared with C45 and R. Conclusion: We conclude that the higher intake of food observed in rats in the growing phase submitted to LPHC diet for 15 days is a consequence of an impairment in the leptin signaling pathways in the hypothalamus, caused by reduction in ObRB and POMC, and that these alterations were not present by the time rats reached adulthood.